Artificial renewal and dynamics of number of wood introductive in Dendropark Trostyanets landscapes - A.A. Iljenko; V.A. Medvedev; A.A. Shulga (Інтродукція Рослин, 2006)
The long-term experience of artificial renewal of wood plants in the Dendropark Trostyanets is generalized. The analysis of survival rate of plantings in terms of an areal of taxon distribution and landscape area of park has been done. It is shown that the artificial renewal, conducted during last decades, does not provide a stable level of number of wood plants in the park.